AUTONOMY AND POWER OF WOMEN BODIES FOR WARANGGANA IN NGANJUK REGENCY - Nida Khoirunisa; Luhung Achmad perguna (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Culture is never separated from the practice of power, as well as Tayub performances. Based on these problems, this article attempts to analyze Waranggana Tayub's bodily autonomy in the private and public spheres and describes how Waranggana Tayub uses power over his body. This research uses descriptive phenomenology method. Data obtained from observations, interviews, and documentation. The results of the study were analyzed using the theory of power relations put forward by Michael Foucault. The results of the study show that Waranggana is able to determine his body autonomy privately and publicly as evidenced by Waranggana determining the boundaries of his body that can be seen and not seen by the audience. In the Tayub performance, there is a game of tug-of-war between Waranggana and Penibing which places Waranggana as both object and subject.